Comparison of Myelotoxicity and Nephrotoxicity Between Daily Low-Dose Cisplatin With Concurrent Radiation and Cyclic High-Dose Cisplatin in Non-Small Cell Lung Cancer Patients - Zazuli, Zulfan; Kos, Renate; Veltman, Joris D.; Uyterlinde, Wilma; Longo, Cristina; Baas, Paul; Masereeuw, Rosalinde; Vijverberg, Susanne J. H.; Maitland-van der Zee, Anke-Hilse (Frontiers in Pharmacology, 2020)
Aim: Antineoplastic effect of cisplatin, the first line treatment in non-small cell lung cancer (NSCLC), is hindered by its nephrotoxicity and myelotoxicity. Both low-dose and high-dose regimens are used in the management of NSCLC. The aim of this study is to assess the risk on myelotoxicity and nephrotoxicity from the daily low-dose cisplatin (DLD) treatment as compared to cyclic high-dose cisplatin (CHD). Methods: A retrospective cohort study was conducted. NSCLC patients treated with cisplatin between 2011 and 2018 in the Amsterdam UMC or Antoni van Leeuwenhoek cancer hospital were studied. Myelotoxicity and nephrotoxicity were defined based on common terminology criteria (CTCAE v4.03) and categorized as ≥grade 1 and ≥grade 2. Modified Poisson regression and Cox proportional hazards model were used to estimate relative risks and cumulative hazard respectively. Results: Of the 115 NSCLC patients receiving DLD (N=62) and CHD (N=53), 60% had ≥grade 1 anemia, 33.9% leukopenia, 31.3% neutropenia, 27.8% thrombocytopenia, 32.2% acute nephrotoxicity with combined definition (Cr-electrolyte nephrotoxicity) and 58.3% chronic nephrotoxicity. The DLD group was older, had an earlier cancer stage, had more comorbidities, and had higher baseline albumin levels. In the DLD group less ≥grade 2 toxicities were reported compared to the CHD group except for Cr-electrolyte nephrotoxicity. However, there was a stronger association in the DLD group with ≥grade 1 leukopenia, thrombocytopenia, and Cr-electrolyte nephrotoxicity. The DLD group developed significantly more ≥grade 1 leukopenia (adjRR=1.83, 95%CI 1.02-3.27), thrombocytopenia (adjRR=3.43, 95%CI 1.64-7.15) and ≥grade 2 Cr-electrolyte nephrotoxicity (adjRR=3.02, 95%CI 1.20-7.56). The DLD group had a lower adjusted cumulative hazard for developing ≥grade 2 myelotoxicity and chronic nephrotoxicity but not for Cr-electrolyte nephrotoxicity (adjHR=3.90, 95%CI 1.35-11.23). In contrast, DLD showed protective effect to ≥grade 2 nephrotoxicity when definition was restricted to the traditional creatinine-based definition (adjRR=0.07, 95%CI 0.01-0.86; adjHR=0.05, 95%CI 0.01-0.56). Conclusions: Overall, the DLD regimen was safer than the CHD regimen when assessing the risk of ≥grade 2 myelotoxicity and nephrotoxicity. However, this might not be the case in patients with a higher risk of electrolyte abnormalities.